Geniposide Alleviates Isoproterenol-Induced Cardiac Fibrosis Partially via SIRT1 Activation in vivo and in vitro - Li, Ning; Zhou, Heng; Ma, Zhen-Guo; Zhu, Jin-Xiu; Liu, Chen; Song, Peng; Kong, Chun-Yan; Wu, Hai-Ming; Deng, Wei; Tang, Qi-Zhu (Frontiers in Pharmacology, 2018)
Objective: Geniposide (GE) is a major component in the fruit of Gardenia jasminoides Ellis. Oxidative stress, endoplasmic reticulum (ER) stress, and canonical Smad3 pathway are implicated in the pathogenesis of cardiac fibrosis. We aim to investigate the protective roles of GE in isoproterenol (ISO)-induced cardiac fibrosis. Methods: ISO was used to induce cardiac fibrosis in male C57BL/6 mice. GE and the EX-527 were given for 2 weeks to detect the effects of GE on cardiac fibrosis. Levels of oxidative stress, ER stress, and Smad3 were evaluated by real time-PCR, Western blots, immunohistochemistry staining, immunofluorescence staining, and assay kits. Results: GE treatment alleviated cardiac dysfunction, fibrosis, and hypertrophy in mice response to ISO. Additionally, GE also suppressed the transformation of cardiac fibroblasts to myofibroblasts stimulated by transforming growth factor-β (TGF-β) in vitro. Mechanistically, GE inhibited the oxidative stress, ER stress, as well as Smad3 pathway activated by ISO or TGF-β. A selective antagonist of sirtuin 1 deacetylase (SIRT1), EX-527, partially counteracted the anti-fibrotic effect and weakened the inhibitory effect on the transformation of cardiac fibroblasts to myofibroblasts after the treatment of GE. Acetylated Smad3 (ac-Smad3), oxidative stress, as well as ER stress pathway were significantly enhanced after SIRT1 was blocked while phosphorylated Smad3 (P-Smad3) was not affected. Conclusion: GE could combat cardiac fibrosis in vivo and in vitro by inhibiting oxidative stress, ER stress, and ac-Smad3 in a SIRT1-dependent manner and suppressing P-Samd3 pathway independent of SIRT1 activation. GE is expected to be a promising agent against cardiac fibrosis.